ANEMIA PADA PENDERITA HIV-AIDS DI POLIKLINIK TERATAI RS HASAN SADIKIN- BANDUNG - Sumantri, Rachmat; Wicaksana, Rudi; Ariantan, Agnes R; Supandiman, Iman; Idjradinata, Ponpon; Creven, Reinout van-; der Ven, Andre van (journal of internal medicine; Vol. 10, No. 3 September 2009)
The prevalence of anemia in HIV-infection ranging between 1.3 ? 95% depend on the stadium of infection. Anemia makes bad impact on morbidity and mortality, and anemia is an independent risk factor for death in HIV-infected patients. A cross-sectional study has been done in Teratai Clinic Hasan Sadikin Hospital to evaluate the prevalence and the etiology of anemia between 1 January to 30 June 2008. Inclusion criteria were all patients who signed the informed consent. There were 534 patients, 222 were anemic, prevalence of anemia was 41.6% (95% CI: 37.4 ? 45.8%), men 167 (72.2%). 188 were mild anemia (Hb 10 ?12/14 g/dl), 26 moderate anemia (Hb 8 ? 10 g/dl), and severe anemia in 6 patients (Hb < 8 g/dl). Anemia of chronic disease or anemia of in! ammation were found in 142 (64.5%) cases, zidovudine related anemia 32 (14.5%) cases, iron de" ciency 14 (6.4%), hemolytic anemia 15 (6.8%) cases, thallassemia 8 (3.6%) cases, and megaloblasic 9 (4.1%) cases. All of anemic patients showed low (< 2) reticulocyt index, high ferritin, low sTfR, and high hs-CRP.
Keywords: HIV-infection, anemia, prevalence, etiology of anemia